2009
DOI: 10.1002/bdrc.20157
|View full text |Cite
|
Sign up to set email alerts
|

Neural induction and factors that stabilize a neural fate

Abstract: The neural ectoderm of vertebrates forms when the BMP signaling pathway is suppressed. Herein we review the molecules that directly antagonize extracellular BMP and the signaling pathways that further contribute to reduce BMP activity in the neural ectoderm. Downstream of neural induction, a large number of “neural fate stabilizing” (NFS) transcription factors are expressed in the presumptive neural ectoderm, developing neural tube, and ultimately in neural stem cells. Herein we review what is known about thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 172 publications
(226 reference statements)
1
75
0
Order By: Relevance
“…Neural induction leads to the upregulation of Zic1, Zic3 and Foxd4l1, which allows ectodermal cells to commit to the neural fate and promotes expression of genes that maintain proliferation in the neural plate at the expense of differentiation (reviewed in Aruga and Mikoshiba, 2011;Moody and Je, 2002;Rogers et al, 2009). Erf-MO and Etv3/3l-MO embryos exhibited lateral expansion of Zic1 (Fig.…”
Section: Erf or Etv3/3l Knockdown Expands Expression Of Neural Progenmentioning
confidence: 99%
See 3 more Smart Citations
“…Neural induction leads to the upregulation of Zic1, Zic3 and Foxd4l1, which allows ectodermal cells to commit to the neural fate and promotes expression of genes that maintain proliferation in the neural plate at the expense of differentiation (reviewed in Aruga and Mikoshiba, 2011;Moody and Je, 2002;Rogers et al, 2009). Erf-MO and Etv3/3l-MO embryos exhibited lateral expansion of Zic1 (Fig.…”
Section: Erf or Etv3/3l Knockdown Expands Expression Of Neural Progenmentioning
confidence: 99%
“…Foxd4l1 upregulates Geminin and Zic2, genes that are known to maintain the neuroectoderm in an immature proliferative state (reviewed by Moody and Je, 2002;Rogers et al, 2009). Erf and Etv3/3l MOs expanded Geminin and Zic2 expression domains (Fig.…”
Section: Erf or Etv3/3l Knockdown Expands Expression Of Neural Progenmentioning
confidence: 99%
See 2 more Smart Citations
“…Amphibian embryos and animal caps are both useful for screening the downstream target genes, which are activated by Ca 2+ signalling during neural induction [20]. In particular, it has been shown that Ca 2+ controls the expression of the immediate early gene c-fos [21] as well as that of two other transcription factors: XlPou2 and zic3 [8].…”
Section: Genes Controlled By Ca 2+mentioning
confidence: 99%